2010
DOI: 10.1111/j.1540-8159.2010.02907.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substance Abuse on Defibrillation Threshold in Patients with Implantable Cardioverter‐Defibrillator

Abstract: Background-The use of recreational drugs has been observed to have deleterious effects on the heart. The aim of our study was to evaluate the effect of substance abuse on the defibrillation threshold (DFT) in patients with implantable cardioverter-defibrillators (ICDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Patients in the high DFT group received a mean of 12.3 ± 7.5 ICD test shocks (range 2-30) compared to 2.0 ± 1.4 shocks (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the satisfactory DFT group (P < 0.0001). The average patient age was 60.2 years, of which the high DFT group was significantly younger (55.6 years vs 60.3 years, P = 0.04) than the satisfactory DFT group.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the high DFT group received a mean of 12.3 ± 7.5 ICD test shocks (range 2-30) compared to 2.0 ± 1.4 shocks (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in the satisfactory DFT group (P < 0.0001). The average patient age was 60.2 years, of which the high DFT group was significantly younger (55.6 years vs 60.3 years, P = 0.04) than the satisfactory DFT group.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…4 Previous studies have shown an association between a high DFT and the severity of left ventricular (LV) dysfunction (measured by increased LV end-diastolic diameter), cocaine use, previous cardiac surgery, impaired renal function, prolonged procedure time, and pneumothorax. [5][6][7][8] Amiodarone use may also be associated with a low defibrillation safety margin. 9 Because of these concerns, some operators still perform device testing at the time of implantation to ensure an adequate safety margin between the successful defibrillation energy and the maximum device output.…”
Section: Introductionmentioning
confidence: 99%
“…This increased rate of hospitalization was also noted to occur in association with an increased rate of cocaine use. Cocaine use is additionally important herein, as detailed previously, because it also increases the defibrillation threshold,24, 37 leading to a reduced likelihood of response to a standard ICD discharge and an increase in mortality.…”
Section: Discussionmentioning
confidence: 88%
“…117 Similarly, studies comparing chronic cocaine users to control patients showed up to 13 joules higher defibrillation threshold in cocaine users receiving ICDs. 118,119 We observed a direct time-dependent correlation between cocaine use and failed ICD therapies. A 36-year-old patient with ischemic cardiomyopathy and ICD implantation 6 years ago was admitted with ventricular tachycardia/ventricular fibrillation storm and multiple ICD shocks, including multiple failed shocks 16 hours after cocaine use with no evidence of ischemia.…”
Section: The Ethics Of Defibrillator Use In Patients With Stimulant U...mentioning
confidence: 79%